2012
DOI: 10.1111/j.1365-2966.2012.21984.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for significant growth in the stellar mass of brightest cluster galaxies over the past 10 billion years

Abstract: Using new and published data, we construct a sample of 160 brightest cluster galaxies (BCGs) spanning the redshift interval 0.03 < z < 1.63. We use this sample, which covers 70 per cent of the history of the universe, to measure the growth in the stellar mass of BCGs after correcting for the correlation between the stellar mass of the BCG and the mass of the cluster in which it lives. We find that the stellar mass of BCGs increases by a factor of 1.8 ± 0.3 between z = 0.9 and z = 0.2. Compared to earlier works… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
257
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(300 citation statements)
references
References 78 publications
39
257
0
Order By: Relevance
“…By comparing the BCGs in our most massive progenitors at z = 1 with our results at z = 0, we find that the BCG grows by around a factor of 5, on average, in our AGN model (mainly by dry mergers). This is significantly higher than the observations, even when sample selection is accounted for (Lidman et al 2012), and requires further investigation. One explanation for these discrepancies is numerical resolution; we will discuss this possibility further in Section 6.…”
Section: Formation History and Distribution Of Starsmentioning
confidence: 62%
See 1 more Smart Citation
“…By comparing the BCGs in our most massive progenitors at z = 1 with our results at z = 0, we find that the BCG grows by around a factor of 5, on average, in our AGN model (mainly by dry mergers). This is significantly higher than the observations, even when sample selection is accounted for (Lidman et al 2012), and requires further investigation. One explanation for these discrepancies is numerical resolution; we will discuss this possibility further in Section 6.…”
Section: Formation History and Distribution Of Starsmentioning
confidence: 62%
“…Lidman et al (2012) find that the mass of BCGs increases by a factor of 1.8 ± 0.3 between z = 0.9 and 0.2. Specifically, the cumulative fraction of stellar mass formed by a given value of a is calculated for each cluster and the median curve is shown, re-scaled to the median final stellar mass.…”
Section: Formation History and Distribution Of Starsmentioning
confidence: 84%
“…11 we show where TXS 2353−003 and NVSS J210626−314003 fall relative to the K − z relationship of Seymour et al (2007) and De Breuck et al (2010), and that of Lidman et al (2012), who found a similar relationship for brightest cluster galaxies (BCGs). This figure shows the good agreement of our targets with both samples, as well as the self-consistency of both samples with each other (as expected if HzRGs are the progenitors of BCGs).…”
Section: K−z Relationshipmentioning
confidence: 91%
“…The full sample comprises 457 cluster members, obtained in 222 h of Gemini time over three years. Analysis of the brightest cluster galaxies in GCLASS is presented in Lidman et al (2012Lidman et al ( , 2013, while the dynamics of the cluster population are considered in papers by Noble et al (2013) and Muzzin et al (2014). The dynamical masses and redshifts of the clusters are shown as blue triangles in Fig.…”
Section: Gclassmentioning
confidence: 99%